2021
DOI: 10.1038/s41598-020-79968-7
|View full text |Cite
|
Sign up to set email alerts
|

4-chlorophenol removal by air lift packed bed bioreactor and its modeling by kinetics and numerical model (artificial neural network)

Abstract: Abstract4-chlorophenol (4-CP) is a hazardous contaminant that is hardly removed by some technologies. This study investigated the biodegradation, and physical 4-CP removal by a mixed microbial consortium in the Airlift packed bed bioreactor (ALPBB) and modeling by an artificial neural network (ANN) for first the time. The removal efficiency of ALPBB was investigated at 4-CP(1-1000 mg/L) and hydraulic retention time (HRT)(6-96 hr) by HPLC. The results showed that removal efficiency decreased from 85 at 1 to 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…In other studies, it has been predicted that microbial populations with 4-9-1 and 3-25-1 structures were used for the removal of toluene and trichloroethylene. Therefore, the results of this study were confirmed by previous studies 30 , 31 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In other studies, it has been predicted that microbial populations with 4-9-1 and 3-25-1 structures were used for the removal of toluene and trichloroethylene. Therefore, the results of this study were confirmed by previous studies 30 , 31 .…”
Section: Resultssupporting
confidence: 91%
“…ANN is a powerful modeling method for determining the nonlinear relationship between variables 30 . This study was performed by feed-forward backpropagation and Levenberg–Marquardt using MATLAB 2018 31 , 32 .…”
Section: Methodsmentioning
confidence: 99%
“…A significant category of these persistent pollutants is represented by refractory organic compounds, which include chlorophenols. They end up in wastewater resulting from the manufacture of pesticides, paints, polymers, cosmetics, etc., and because they cannot be removed by conventional methods in wastewater treatment plants, they arrive in natural water bodies [3,4].…”
Section: Introductionmentioning
confidence: 99%